Любимые волшебные сказки - Нечитайло Виктор (Лучшие стихи и сказки малышам, 2009)
Экземпляры: ФО-3 (201403) / Инвентарный номер: 49180 / Цена: 50.00 / Сис.шифр: Р2 / Авт.знак: Л 93 / ГРНТИ: 17.82 / ББК: 84(2Рос.Рус)44